New appointments beginning AY 2011-2012 - De La Salle University, Manila (Animo Repository, 2011)
De La Salle University President, Br. Narciso S. Erguiza, Jr. FSC announced the appointment of Dr. Arnulfo P. Azcarraga to the new position of Vice Chancellor for research effective 16 May 2011. This position establishes the separation of the dual positions (Academics and Research) lodged in the Vice Chancellor for Academics and Research. Dr. Myrna S. Austria remains as the Vice Chancellor for Academics. The vacated position of Dr. Azcarraga as EVP for External Linkages and Internationalization will be occupied by Dr. Alvin B. Culaba, effective 16 May 2011.